Дифузна неходжскінська лімфома надниркових залоз у клінічній практиці - Товкай, О. А.; Черенько, С. М. (Clinical Endocrinology and Endocrine Surgery, 2014)
Diffuse non-Hodgkin’s adrenal lymphoma is very rare disease (less than 100 cases described), which is characterized by bilateral involvement, fast growth which is accompanied by chronic adrenal insufficiency. Short review on clinics and diagnosis based on own practice was presented.